Estrategias Metodológicas para potenciar el rendimiento académico en el área de Matemática. - Clavijo Castro, Rosario Cecilia (2022)
The present research work addresses the low academic performance in the area of Mathematics of the students of the fourth year of Basic General Education of the Educational Unit "Emilio Terán", being a relevant factor that intervenes in the problem the non-use of active Methodological Strategies. by teachers, for which the implementation of Methodological Strategies is proposed to strengthen the teaching-learning process of basic operations. The methodology used is the quantitative and qualitative approach, information is collected through bibliographic analysis and interpretation, analysis of products and techniques such as the diagnostic test, surveys, interviews, focused on the student and educational actors that are later analyzed and interpreted through the statistics to establish percentage calculations. With this, it is possible to specify methodological strategies to enhance academic performance in the area of Mathematics, to provide alternative solutions with the aim of dynamizing, optimizing the teaching-learning process and reducing the rate of students with low academic performance in basic operations. in the area of Mathematics.